Management of conflicts arising from disclosure of HIV status among married women in Southwest Nigeria. (2013)
This study examined if disclosure to their spouses by married women living with HIV/AIDS resulted in conflicts. Fifty-seven women completed a questionnaire on conflict indicators. While 93% disclosed their status within 6 months of diagnosis, 12.3% did so through a third party. More than thirty-six percent (36.8%) confirmed that disclosure led to conflict. Although 19.3% had their conflicts resolved through a third party, 10% suffered separation. Marital status and fear of stigma significantly influence time to disclose (p < .01 and p < .05), while type of marriage strongly influences whether status will be disclosed (p < .01). Programs for women with HIV should consider conflicts that may arise from disclosure.